FORMULASI VARIASIONAL DAN PENYELESAIAN DARI MASALAH SYARAT BATAS DARI PERSAMAAN ORDER DUA - sutrima, sutrima (MATEMATIKA, 2002)
The purpose of this research is to investigate solutions of boundary value problems of second-roder differential operator byÂ  variational methods. Using variational formulation of the problems, existence of solutions of boundary value problems of second-order differential operator can be obtained.Â